EFEKTIVITAS-BIAYA PENGGUNAAN BEVACIZUMAB DAN RANIBIZUMAB SEBAGAI ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR PADA PASIEN DENGAN GANGGUAN MATA: TINJAUAN SISTEMATIS - Cahyono, Nur Sidik; Sukandar, Elin Yulinah (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2024)
Anti-vascular endothelial growth factor (VEGF) given by intravitreal injection can be used to treat patients with eye disorders. The anti-VEGF drugs used include bevacizumab, ranibizumab, aflibercept, and brolucizumab. These drugs are high-cost drugs, so the cost-effectiveness of each drug must be considered in order to save on treatment costs. This systematic review aims to provide a comprehensive picture of the cost-effectiveness of bevacizumab and ranibizumab. The databases used to identify relevant studies are PubMed, Science Direct and Google Scholar. This research is limited to randomized control trials (RCT), clinical trials, and research articles, studies that explain the cost-effectiveness of intravitreal injections of bevacizumab and ranibizumab and other drugs as anti-VEGF for patients with eye disorders, as well as articles in English. Electronic data-based searches resulted in 2414 articles; 27 articles were selected that had full text access and discussed the cost-effectiveness of ranibizumab or bevacizumab, but only 12 articles suitable for inclusion were considered. Bevacizumab is more cost-effective than ranibizumab.